2021
DOI: 10.1097/jxx.0000000000000625
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and quality of life in lung cancer patients and survivors

Abstract: Background: Lung cancer patients and survivors are vulnerable to disturbed sleep and impaired quality of life (QOL) across the continuum of illness. Few studies have sought to identify predictors of QOL using well-validated measures of both sleep quality and QOL in this population. Purpose: The purpose of this study was to examine factors associated with lung cancer that are predictive of QOL in adult lung cancer patients and survivors in the outpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…e study also concluded that the quality of life of the intervention group after nursing was significantly better than that of the control group (P < 0.001), which was consistent with the founding of Bowden J et al In their study, the patients in the experimental group accepted conventional nursing combined with oculomotor training, and the patients in the control group accepted conventional nursing only, and the results showed that the quality of life after nursing of the experimental group was obviously higher than that of the control group (95.87 ± 2.11 vs 80.57 ± 4.12, P < 0.001) [25], indicating that the combined mode could promote the quality of life and patient satisfaction with nursing by improving their sleep quality and enhancing their body immunity. Widely applying the conventional nursing combined with oculomotor training can lower the possibility of nursing disputes and provide patients with more efficient and scientific nursing.…”
Section: Discussionsupporting
confidence: 89%
“…e study also concluded that the quality of life of the intervention group after nursing was significantly better than that of the control group (P < 0.001), which was consistent with the founding of Bowden J et al In their study, the patients in the experimental group accepted conventional nursing combined with oculomotor training, and the patients in the control group accepted conventional nursing only, and the results showed that the quality of life after nursing of the experimental group was obviously higher than that of the control group (95.87 ± 2.11 vs 80.57 ± 4.12, P < 0.001) [25], indicating that the combined mode could promote the quality of life and patient satisfaction with nursing by improving their sleep quality and enhancing their body immunity. Widely applying the conventional nursing combined with oculomotor training can lower the possibility of nursing disputes and provide patients with more efficient and scientific nursing.…”
Section: Discussionsupporting
confidence: 89%
“…Breast cancer is widespread among Bahraini females; around 37.1% of all cancers are breast-related (Martin et al, 2021). Annually around 54.4 per 100,000 people are diagnosed with breast cancer worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…To circumvent and alleviate Total Mood Disturbance (TMD), patients should be educated on how relaxation, meditation and yoga can be helpful. The scores represented a 13% reduction in overall mood disturbance for the participants after practicing meditation (Martin, Loomis, & Dean, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The findings were consistent with the other studies that employed LC patients and survivors with other stages. [17][18][19]25,47 In addition, this study used the Taiwan version of WHOQOL-BREF and MDASI to explore the association between HRQOL and SB among newly diagnosed LC patients. The findings may be used as references for accessible clinical care to improve the quality of life of all LC patients.…”
Section: Discussionmentioning
confidence: 99%
“…13 These factors include demographic factors (age, gender, educational level, and smoking status), disease factors (cancer stage, treatment, and performance status), [14][15][16] symptom burden (SB; symptom severity and interference), [17][18][19][20] psychological distress (depression and anxiety), 21,22 physical activity, 23,24 and sleep quality. 25,26 Compared to the quantity of available literature on the HRQOL of patients diagnosed with other major cancers, few studies have explored the HRQOL and its related factors among newly diagnosed LC patients before treatment. Hence, this study aimed to examine the relationships between the SB, physical activity (PA), sleep quality (SQ), and HRQOL among newly diagnosed LC patients.…”
Section: Introductionmentioning
confidence: 99%